2024
DOI: 10.1002/adfm.202401562
|View full text |Cite
|
Sign up to set email alerts
|

Structural Motifs in Covalent Organic Frameworks for Photocatalysis

Liyang Qin,
Chengdi Ma,
Jian Zhang
et al.

Abstract: Covalent organic frameworks (COFs) attract significant attention due to their ordered, crystalline, porous, metal‐free, and predictable structures. These unique characteristics offer great opportunities for the diffusion and transmission of photogenerated charges during photocatalysis. Currently, a considerable number of COFs are used as metal‐free organic semiconductor photocatalysts. This review aims to understand the relationships between the structure and photocatalysis performance of COFs and provides in‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 380 publications
0
0
0
Order By: Relevance
“…Additionally, the planar molecular configuration of crystalline COFs notably mitigates spatial site resistance effects and conformational freedom, thereby facilitating axial electron migration. 21 Furthermore, the tunable local charge density, coupled with the electron push-pull effect, furnishes kinetic energy for charge migration while diminishing exciton binding and carrier complexation efficiencies.…”
Section: Optimal Separation Of Carriers and Enhancement Of Transport ...mentioning
confidence: 99%
“…Additionally, the planar molecular configuration of crystalline COFs notably mitigates spatial site resistance effects and conformational freedom, thereby facilitating axial electron migration. 21 Furthermore, the tunable local charge density, coupled with the electron push-pull effect, furnishes kinetic energy for charge migration while diminishing exciton binding and carrier complexation efficiencies.…”
Section: Optimal Separation Of Carriers and Enhancement Of Transport ...mentioning
confidence: 99%
“…23 Despite the increasing attention directed towards the application of COF nanosheets in photocatalysis, the exploration of COF-based composites for catalyzing organic transformations is still in its infancy. 24–27 Meanwhile, most studies have only demonstrated the overall photocatalytic performance, with COFs either serving as a photosensitizer or as a solid support, and examples of COFs acting as intrinsic catalysts are relatively scarce. 28 Moreover, the elucidation of the synergistic effects, such as detailed spectroscopic comprehension of exciton and charge carrier dynamics, which are crucial for advancing photocatalytic processes, remains largely unexplored.…”
Section: Introductionmentioning
confidence: 99%